2020
DOI: 10.4018/978-1-7998-3062-7.ch005
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Language Learning Strategies in Technology-Enhanced Learning Environment

Abstract: This chapter reports on the Yemeni and Saudi EFL learners' use of language learning strategies (LLSs) in technology-mediated language learning contexts. The study examines whether nationality and gender play a significant role in using LLSs on electronic platforms. The study adopted a correlative design in which 100 Yemeni and Saudi university students were recruited to respond to an online close-ended questionnaire. Drawing on Oxford's classification of learning strategies, the findings of this study showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…The study also revealed that only male students used such strategies, primarily because female students in Yemen may not talk with males on social media, and some students may not be allowed to own a mobile because of their conservative customs. In a previous study, Bin-Hady et al (2020) found that Yemeni EFL learners use LLSs in technology environments less than their Saudi counterparts. They justified such finding by the lack of technology infrastructure in the Yemeni learning context as opposed to the rich availability of such technologies in the Saudi context.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…The study also revealed that only male students used such strategies, primarily because female students in Yemen may not talk with males on social media, and some students may not be allowed to own a mobile because of their conservative customs. In a previous study, Bin-Hady et al (2020) found that Yemeni EFL learners use LLSs in technology environments less than their Saudi counterparts. They justified such finding by the lack of technology infrastructure in the Yemeni learning context as opposed to the rich availability of such technologies in the Saudi context.…”
Section: Discussionmentioning
confidence: 89%
“…The study revealed that students used the informal learning strategy of accessing social media like watching movies and other audiovisual resources. In the Arab educational contexts, Bin-Hady et al (2020) explored the use of LLSs with technology in two settings, Yemen and Saudi Arabia. The study found that Saudi EFL learners used LLSs more than the Yemenis.…”
Section: Informal Learning Strategies and Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…Social networking sites like Google, Twitter, YouTube, Facebook, and LinkedIn hold a great deal of promise to help students learn online by helping them access information they can use to enrich, develop, edit, and sharpen their knowledge (Bin-Hady & Al-Tamimi, 2021;Gaytan, 2013). With the rapid development of technology and the meteoric popularity of social media, there are diverse opportunities today to evaluate learning and inspire learners (Bin-Hady et al, 2020;Gikas & Grant, 2013).…”
Section: Introductionmentioning
confidence: 99%